Crow trap - Cleeves, Ann (New York Minotaur Books, 2017)
Three very different women come together to complete an environmental survey. Three women who, in some way or another, know the meaning of betrayal ... For team leader Rachael Lambert the project is the perfect opportunity to rebuild her confidence after a double-betrayal by her lover and boss, Peter Kemp. Botanist Anne Preece, on the other hand, sees it as a chance to indulge in a little deception of her own. And then there is Grace Fulwell, a strange, uncommunicative young woman with plenty of her own secrets to hide ... When Rachael arrives at the cottage, however, she is horrified to discover the body of her friend Bella Furness. Bella, it appears, has committed suicide--a verdict Rachael finds impossible to accept. Only when the next death occurs does a fourth woman enter the picture--the unconventional Detective Inspector Vera Stanhope, who must piece together the truth from these women's tangled lives in The Crow Trap . Ann Cleeves's popular Vera Stanhope books have been made into the hit series "Vera" starring Brenda Blethyn and are available in the U.S.
"A Thomas Dunne book."
113567
Keywords: Stanhope, Vera -- Fiction; Women -- England -- Pennine Chain -- Fiction; Murder -- Investigation -- England -- Pennine Chain -- Fiction; Murder -- Investigation; Women; England -- Pennine Chain; Detective and mystery stories; Fictional Work; Fiction; Novels; Mystery fiction